Prospects of Levetiracetam as a Neuroprotective Drug Against Status Epilepticus, Traumatic Brain Injury, and Stroke - Shetty, Ashok K. (Frontiers in Neurology, 2013)
Levetiracetam (LEV) is an antiepileptic drug commonly used for the treatment of partial onset and generalized seizures. In addition to its neuromodulatory and neuroinhibitory effects via its binding to the synaptic vesicle protein SV2A, multiple studies have suggested neuroprotective properties for LEV in both epileptic and non-epileptic conditions. The purpose of this review is to discuss the extent of LEV-mediated protection seen in different neurological conditions, the potential of LEV for easing epileptogenesis, and the possible mechanisms that underlie the protective properties of LEV. LEV has been found to be particularly beneficial for restraining seizures in animal models of spontaneous epilepsy, acute seizures and status epilepticus (SE). However, its ability for easing epileptogenesis and cognitive dysfunction following SE remains controversial with some studies implying favorable outcomes and others reporting no beneficial effects. Efficacy of LEV as a neuroprotective drug against traumatic brain injury (TBI) has received much attention. While animal studies in TBI models have showed significant neuroprotection and improvements in motor and memory performance with LEV treatment, clinical studies suggest that LEV has similar efficacy as phenytoin in terms of its ability to prevent post-traumatic epilepsy. LEV treatment for TBI is also reported to have fewer adverse effects and monitoring considerations but electroencephalographic recordings suggest the presence of increased seizure tendency. Studies on stroke imply that LEV is a useful alternative to carbamazepine for preventing post-stroke seizures in terms of efficacy and safety. Thus, LEV treatment has promise for restraining SE- TBI- or stroke-induced chronic epilepsy. Nevertheless, additional studies are needed to ascertain the most apt dose, timing of intervention and duration of treatment after the initial precipitating injury and the mechanisms underlying LEV-mediated beneficial effects.